Estimating ground reaction forces from gait kinematics in cerebral palsy: a convolutional neural network approach - Özateş, Mustafa Erkam; Salami, Firooz; Wolf, Sebastian Immanuel; Arslan, Yunus Ziya (Annals of biomedical engineering, 2025)
While gait analysis is essential for assessing neuromotor disorders like cerebral palsy (CP), capturing accurate ground reaction force (GRF) measurements during natural walking presents challenges, particularly due to variations in gait patterns. Previous studies have explored GRF prediction using machine learning, but specific focus on patients with CP is lacking. This research aims to address this gap by predicting GRF using joint angles derived from marker data during gait in patients with CP, thereby suggesting a protocol for gait analysis without the need for force plates.